Situations : a model for the analysis of mental hospital practices - Papenfus, Stanley Charles (Department of Psychology, 2015)
The thesis as a whole aims to demonstrate that the socialization model, presented in Chapter VIII, is an appropriate model for use in analysing mental hospital practices and that the classificatory schema based on it is appropriate for describing the processes at work in these practices. The classificatory schema itself takes into account (a) culturally embedded criteria for assessing patient behaviour and patterns of construing, (b) culturally embedded means of 'shaping' patient behaviour and patterns of construing, (c) culturally embedded forms of ambiguity latently presented in the appraising and shaping of patient behaviour and patterns of construing and (d) the potential ways in which this ambiguity can interfere with the process of patient resocialisation itself. The model serves to focus attention on two existential problems which members of staff face in committing themselves to their institutional roles: that of disclosing therapeutic rationale to patients and that of embodying this rationale in concrete commitments to patients.